Physical workload, low back pain and neck–shoulder pain: a Swedish twin study. Issue 6 (5th December 2008) - Nyman, T; Mulder, M; Iliadou, A; Svartengren, M; Wiktorin, C
Abstract : Objectives: To investigate if high physical workload is associated with low back pain (LBP) and/or neck–shoulder pain (NSP) when taking into account the influence of genetic and shared environmental factors. Further, the study aims to explore the potential influence of genetic and shared environmental factors in the associations between high physical workload and the three disorder subgroups: solely LBP, solely NSP, and concurrent LBP and NSP. Methods: Data on 16 107 monozygotic and dizygotic twins, born during 1959–1985, were obtained from a cross-sectional study, performed in 2005–2006 by the Swedish Twin Registry. Odds ratios (ORs) calculated in cohort analyses and co-twin control analyses were used to assess the associations between high physical workload and LBP and NSP when controlling for genetic and shared environmental factors. Results: In the cohort analysis, the association between high physical workload and the group with any one symptom (LBP and/or NSP) was OR 1.47 (95% CI 1.37 to 1.57). The co-twin control analyses indicated that the association was not confounded by genetic and shared environmental factors with OR 1.34 (95% CI 1.02 to 1.75) for dizygotic twins and OR 1.44 (95% CI 1.06 to 1.95) for monozygotic twins. In the cohort analyses the association with high physical workload was higher for concurrent LBP and NSP (OR 1.80 (95% CI 1.62 to 1.99)) than for solely LBP (OR 1.41 (95% CI 1.27 to 1.57)) and solely NSP (OR 1.31 (95% CI 1.20 to 1.43)). Concurrent LBP and NSP was the only group that showed a stepwise decrease of the point estimates between the cohort analysis and the co-twin control analyses, OR 1.71 (95% CI 1.00 to 2.94) for dizygotic twins, and OR 1.29 (95% CI 0.64 to 2.59) for monozygotic twins indicating confounding by genetic and shared environmental factors. Conclusions: High physical workload was associated with LBP and/or NSP even after adjusting for genetic or shared environmental factors. Only for concurrent LBP and NSP, genetic and shared environmental factors seemed to have an influence on the association with high physical workload.